Controlling the Valence‐Electron Arrangement of Nickel Active Centers for Efficient Hydrogen Oxidation Electrocatalysis. Issue 32 (4th July 2022) - Zhao, Xu; Li, Xiangyang; An, Lulu; Zheng, Lirong; Yang, Jinlong; Wang, Deli
Abstract: The valence‐electron arrangement of heterogeneous catalysts can significantly affect the binding behavior of absorbates. However, it remains a challenge to understand the role of the valence‐electron arrangement in electrocatalysis, which limits its utilization as a tool to design efficient electrocatalysts. Here, we describe experiments in which the valence‐electron arrangement of Ni active centers for hydrogen oxidation is controlled precisely by using Ni‐vacancy‐enriched Ni3 N as a platform. These Ni vacancies can promote the valence‐electron delocalization of OH‐adsorption centers to enhance the Ni  ds –O 2 p valence‐electron‐orbital interaction with elevated OH adsorption. Meanwhile, the deficit of valence‐electrons of H‐adsorption centers at Ni vacancies can lower Ni  ds –H 1 s interaction with weakened H binding. Relative to Ni3 N poor in vacancies, the Ni‐vacancy‐enriched Ni3 N showed a mass activity enhanced by 15‐fold. This strategy paves a rational way to design efficient catalysts by finely tuning the valence‐electron arrangement. Abstract : The valence‐electron arrangement of Ni active centers can be controlled precisely by introducing Ni vacancies into electrocatalysts for facilitated hydrogen oxidation. Benefiting from the optimized valence‐electron‐orbital interactions with key intermediates, the Ni‐vacancy‐enriched Ni3 N exhibited a 15‐fold enhanced mass activity in comparison with Ni3 N which has far fewer Ni vacancies.